A mediação como instrumento concretizador do direito fundamental à saúde: uma alternativa à judicialização de conflitos Natal 2013 - Queiroz, Cláudia Carvalho (2013)
In Brazil, the 1946 Constitution enshrined the right to health, having it defined as the possession of the best state of health that the individual can achieve. Already the Federal Constitution of 1988 lifted that right to the status of fundamental social right, which transcends the effectiveness and cure of the disease is based on the joint liability of public entities for the provision of a quality service, efficient and prioritize human dignity and comprehensive evaluation of patients. According to the World Health Organization, the definition of health, first characterized as the mere absence of disease, has become recognized as the need to search for preventive mechanisms to ensure the welfare and dignity of the population. Garantista this context, the growing seem lawsuits that deal with the implementation of public policies, especially in the area of the right to health, the omission of which the Government can result in the risk of death. Hence the concern of law professionals about whether or not the intervention of the judiciary in cases that deal with providing material benefits of health care. It claims to break the principle of separation of powers, disobedience to the principle of equality and the impossibility of judicial intervention in the formulation of public policy to try and exclude the liability of public entities. In contrast, the judiciary has repeatedly guardianships granted injunctions or merit determining the supply of materials indicated by the medical benefits that accompany the treatment of patients who resort to a remedy. In this context, mediation, object of study and resolution presented in this work, is presented as an instrument conciliator between the reserve clause and the right to financially possible existential minimum, as it seeks to serve all through rationalization of health services , avoidance of negativistic influence of the pharmaceutical industry, with prioritizing the welfare of the individual and the quality of relationships. This is alternative way to judicialization that in addition to encouraging and developing active citizen participation in public policy formulation also allows the manager to public knowledge of community needs. It is in this sense that affirms and defends the right to health is no longer the mere provision of medical care and prescription drugs, but a dialogue conscious existential minimum to guarantee a dignified life